Asphalt binder and mixture performance using Batu Pahat soft clay as modifier - Al Allam, Allam Musbah (2017)
Road construction is required to provide better mobility for the community. This research aims to evaluate the use of BPSC particles as additive in Hot Mix Asphalt (HMA) mixture which was previously introduced in powder form. The experimental work for this survey included the use of four BPSC ratios (2, 4, 6 and 8%) according to the weight of bitumen. A design for the hot mix asphalt was executed by using the Superpave method for each additive ratio. However, using soft clay as filler to modify asphalt binder and mixture was not intensively done by researchers. Additionally, physical properties results of penetration and softening point show that soft clay can increase the binder stiffness, while storage stability of modified asphalt binder had a good compatibility between the original and modified binder. The rheological properties results such as dynamic shear rheometer indicated that soft clay modified asphalt binder would increase the stiffness and the elastic behavior compared to unmodified binder at intermediate and high temperatures. It has also the lowest susceptibility for rutting and the temperature susceptibility. In addition, microstructure examinations of the asphalt binders were then achieved by using scanning electron microscopy, hence; images displayed that soft clay particles distributed uniformly in the asphalt matrix. In addition, asphalt mixture test such as indirect resilient modulus, indicated that the stiffness increased as the percentages of soft clay increased. Also, dynamic creep results showed that the adding soft clay to asphalt mixtures remarkably decreases its susceptibility to permanent deformation. As for the moisture susceptibility, all the samples pass the 80% tensile strength ratio, it could be noted that BPSC had improved adhesion strength between an aggregate and binder. Furthermore, ageing index values show that the susceptibility to oxidative ageing was significantly reduced with the increase of BPSC content after short-term aging, and also it was observed that short-term aging had given a good resistance to oxidation. Studies on correlation analysis between different rheological modified asphalt binder and mixture of HMA were also conducted. It was shown that a strong correlation exists among G*/sin δ and rut depth. In conclusion, the introduction of BPSC has a bright potential as a new material of HMA which can be used in pavement construction in the future.